Room-temperature phosphorescence of a water-soluble supramolecular organic framework. Issue 79 (15th September 2021) - Xu, Chen; Lin, Xiaohan; Wu, Wenjun; Ma, Xiang
Abstract : A porous water-soluble supramolecular organic framework efficiently exhibiting phosphorescence was developed both in an aqueous phase and in film state at room-temperature. Abstract : A flexible porous water-soluble supramolecular organic framework was developed, which could efficiently exhibit phosphorescence both in an aqueous phase and in a film state at room-temperature.